Authorea
DOI: 10.22541/au.158152202.25576908
|View full text |Cite
|
Sign up to set email alerts
|

Rapid adaptive evolution to drought in a subset of plant traits in a large-scale climate change experiment

Abstract: Rapid evolution of traits and of plasticity may enable adaptation to climate change, yet solid experimental evidence under natural conditions is scarce. Here, we imposed rainfall manipulations (+30%, control, -30%) for ten years on entire natural plant communities in two Eastern Mediterranean sites. Additional sites along a natural rainfall gradient and controlled selection analyses assessed whether potential responses were adaptive. In both sites, our annual target species Biscutella didyma consistently evolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 36 publications
0
13
1
Order By: Relevance
“…For example, successful recovery in density of plant communities in France significantly differed between lowland and highland forests in response to warming (Bertrand et al, 2011). On the other hand, desert annuals (e.g., the Californian Brassica rapa ) have been shown to rapidly evolve other traits (e.g., flowering time) to cope with drought-like conditions (Sultan et al, 2013; Hamann et al, 2018; Dickman et al, 2019; Metz et al, 2020); such adaptations may give species enough time to adapt other traits, such as germination rates, to evolutionarily stable strategies, especially since evolution can occur on much shorter time-scales (e.g., decadal) than previously expected (Hamann et al, 2018; Hendry, 2016; Shaw and Etterson, 2012). Thus, a mix of phenotypic and evolutionary adaptation may help buffer such species until they successfully adapt their germination strategies to new regimes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, successful recovery in density of plant communities in France significantly differed between lowland and highland forests in response to warming (Bertrand et al, 2011). On the other hand, desert annuals (e.g., the Californian Brassica rapa ) have been shown to rapidly evolve other traits (e.g., flowering time) to cope with drought-like conditions (Sultan et al, 2013; Hamann et al, 2018; Dickman et al, 2019; Metz et al, 2020); such adaptations may give species enough time to adapt other traits, such as germination rates, to evolutionarily stable strategies, especially since evolution can occur on much shorter time-scales (e.g., decadal) than previously expected (Hamann et al, 2018; Hendry, 2016; Shaw and Etterson, 2012). Thus, a mix of phenotypic and evolutionary adaptation may help buffer such species until they successfully adapt their germination strategies to new regimes.…”
Section: Discussionmentioning
confidence: 99%
“…Clinal divergence of drought escape and avoidance traits in capeweed show parallels with the trait divergence documented in a 10‐yr experimental evolution study (using Biscutella didyma ; Metz et al ., 2020), which reported rapid divergence in flowering phenology and allocation to reproduction, yet no divergence in water conservation traits. Their results and ours suggest that drought escape, which is driven predominantly by plant phenology, may be more evolutionarily labile than dehydration avoidance strategies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta‐analysis of > 200 studies and 7000 estimates of directional selection from globally distributed field populations (primarily terrestrial plants and animals) showed that climatic extremes associated with precipitation and evapotranspiration are correlated with temporal and spatial variation for directional selection (Siepielski et al ., 2017), making water stress a compelling candidate environmental variable mediating selection and local adaptation. Although meta‐analyses of manipulative experiments confirm that abiotic factors profoundly affect directional selection (Caruso et al ., 2017, 2020), few experiments have convincingly isolated effects of water stress from other environmental variables (Heschel et al ., 2004; Volis et al ., 2004; Heschel & Riginos, 2005; Sherrard & Maherali, 2006; Brachi et al ., 2012; Ivy & Carr, 2012; Kenney et al ., 2014; Lambrecht et al ., 2017; Hamann et al ., 2018; Metz et al ., 2020). Even fewer have estimated both clinal divergence and selection from manipulative experiments to test whether water stress reliably predicts geographical divergence in nature (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such regions, water availability is the major control over seasonal plant growth and is a key factor shaping the evolution of emergence timing within and among years (Arroyo et al., 2006; Petrů & Tielbörger, 2008; Torres‐Martínez et al., 2017). Plant populations toward the drier ends of aridity gradients tend to experience shorter windows of favorable environmental conditions (Aviad et al., 2004; Metz et al., 2020) as well as greater interannual variability in conditions than populations occupying more mesic sites (Davidowitz, 2002; Metz et al., 2020). As a result, more arid sites might select for earlier emergence within years to facilitate rapid growth (Dickman et al., 2019; Sexton et al., 2011), greater spread of emergence among years as a way of bet‐hedging (Arroyo et al., 2006; Petrů & Tielbörger, 2008; Venable & Brown, 1988), or both, which could lead to constrained adaptive evolution.…”
Section: Introductionmentioning
confidence: 99%